Quaternionic fractional Fourier transform for Boehmians - Roopkumar, R. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 517.9We construct a Boehmian space of quaternion valued functions using the quaternionic fractional convolution. Applying the convolution theorem, the quaternionic fractional Fourier transform is extended to the context of Boehmians and its properties are established.